Instrumented trunk impairment scale (iTIS): A reliable measure of trunk impairment in the stroke population. Issue 6 (18th August 2021) - Alhwoaimel, Norah; Turk, Ruth; Hughes, Ann-Marie; Ferrari, Federico; Burridge, Jane; Wee, Seng Kwee; Verheyden, Geert; Warner, Martin
ABSTRACT: Background: The Trunk Impairment Scale (TIS) is recommended for use in clinical research to assess trunk impairment post-stroke. However, it is observer dependent and does not consider the quality of trunk movement. To address these challenges, this study proposes an instrumented TIS (iTIS). Objective: This study aims to investigate the intra-rater and inter-rater reliability of the iTIS in chronic stroke patients. Method: Trunk impairment was assessed in 20 patients with stroke using the iTIS Valedo system; three sensors were fixed to the skin on the sternum, L1 and S1 levels. Interclass correlation coefficients were used to assess the inter-rater and intra-rater reliability (between days) with 95% CI. Results: Reliability for the dynamic subscale parameters was good to excellent (intra-rater ICC = 0.60–0.95; inter-rater ICC = 0.59–0.93); however, reliability for the coordination parameters was poor to good (intra-rater ICC = 0.05–0.72) and poor to excellent (inter-rater ICC = 0.04–0.78). Conclusion: The iTIS demonstrates an acceptable level of reliability for dynamic subscale measurement in research and clinical practice. Further studies could use larger sample sizes and improve the iTIS methodology by employing additional sensors on the limbs to detect compensatory movements.